Platelet Transfusion in Clinical Practice: A Narrative Literature Review - Willim, Herick Alvenus; Wandi (Open Access Indonesian Journal of Medical Reviews, 2023)
Platelet transfusion plays a vital role in clinical practice, serving as a cornerstone in the management of various medical conditions. Thrombocytopenia, characterized by a low platelet count, can result from decreased platelet production, increased peripheral platelet destruction, increased splenic sequestration, or dilutional thrombocytopenia. Platelet transfusion is commonly administered for prophylactic purposes to prevent bleeding in patients with hypoproliferative thrombocytopenia and before invasive procedures or surgeries. In cases of bleeding or significant bleeding risk, therapeutic platelet transfusion is employed. This review article aims to provide an understanding of platelet transfusion and its applications in daily clinical practice. The dosage and administration of platelet transfusion, as well as potential complications, are discussed. Understanding the indications, contraindications, and appropriate use of platelet transfusion is crucial for optimizing patient outcomes and ensuring safe and effective clinical practice.